WebPropagate: A Web Server for Network Propagation. Issue 15 (20th July 2018) - Biran, Hadas; Almozlino, Tovi; Kupiec, Martin; Sharan, Roded
Abstract: Network propagation is a powerful tool for genetic analysis which is widely used to identify genes and genetic modules that underlie a process of interest. Here we provide a graphical, web-based platform (http://anat.cs.tau.ac.il/WebPropagate/ ) in which researchers can easily apply variants of this method to data sets of interest using up-to-date networks of protein–protein interactions in several organisms. Graphical abstract: Highlights: We propose WebPropagate: a web server that implements network propagation on up-to-date protein–protein interaction networks of four species. WebPropagate produces p -values for the propagation results and corrects them for multiple testing, allowing the identification of significant proteins. WebPropagate produces a graphical display of the subnetwork connecting the significant proteins, facilitating the interpretation of the results.